Lymph node ratio and preoperative CA 19-9 levels predict overall survival and recurrence-free survival in patients with resected pancreatic adenocarcinoma - Wentz, Sabrina C (Baishideng Publishing Group Co., Limited, 2012)
AIM: Clinicopathologic factors predicting overall survival (OS) would help identify a subset to benefit from adjuvant therapy. METHODS: One hundred and sixty-nine patients patients from 1984 to 2009 with curative resections for pancreatic adenocarcinoma were included. Tumors were staged by American Joint Committee on Cancer 7th edition criteria. Univariate and multivariable analyses were performed using Kaplan-Meier methodology or Cox proportional hazard models. Log-rank tests were performed. Statistical inferences were assessed by two-sided 5% significance level. RESULTS: Median age was 67.1 (57.2-73.0) years with equal gender distribution. Tumors were in the head (89.3%) or body/tail (10.7%). On univariate analysis, adjuvant therapy, lymph node (LN) ratio, histologic grade, negative margin status, absence of peripancreatic extension, and T stage were associated with improved OS. Adjuvant therapy, LN ratio, histologic grade, number of nodes examined, negative LN status, and absence of peripancreatic extension were associated with improved recurrence-free survival (RFS). On multivariable analysis, LN ratio and carbohydrate antigen (CA) 19-9 levels were associated with OS. LN ratio was associated with RFS. CONCLUSION: The LN ratio and CA 19-9 levels are independent prognostic factors following curative resections of pancreatic cancer.